The Human Rights Situation of Indigenous Peoples in Africa (Fourth World Journal, 1989)
This article highlights the legacy of Grand Chief George Manuel, focusing on his role in mobilizing Indigenous communities to advocate for self-government and Indigenous rights. It also examines the human rights situation of Indigenous Peoples in Africa, emphasizing the ongoing impact of colonialism and neo-colonial relationships on their lives. Additionally, the article explores the intersection of Marxist theory and practice with Indigenous struggles, underscoring the importance of cultural identity, unity, and resistance in the fight for Indigenous rights. By linking these diverse contexts, the study sheds light on global Indigenous movements and the continuing challenges they face due to cultural intolerance and political marginalization.